Non-Targeted Metabolomics Analysis of Small Molecular Metabolites in Refrigerated Goose Breast Meat - Dongzhi Miao; Xuebei Wu; Kui Zuo; Jing Chen; Ying Wang; Junhua Pu; Haiming Yang; Zhiyue Wang (Veterinary Sciences)
Poultry represents a rich source of multiple nutrients. Refrigeration is commonly employed for poultry preservation, although extended storage duration can adversely affect the meat quality. Current research on this topic has focused on the analysis of biochemical indices in chilled goose meat, with limited information on changes in metabolites that influence the quality of the meat during storage. This study used non-targeted metabolomics and the random forest algorithm to investigate metabolite changes in goose meat over an extended storage period. The results showed a significant change in the composition of the meat as the duration of storage increased, with the identification of 121 distinct metabolites. Further analysis identified 18 metabolites that could be used as indicators of the degradation of carbohydrates, amino acids, nucleotides, and lipids. These metabolites could be used as markers to monitor the deterioration process. These intermediate metabolites tended to be transformed into lower-level products involving pyruvate, acetyl coenzyme A, and fumaric acid, used in the tricarboxylic acid cycle, performing substance transformation. This comprehensive analysis of metabolites provides a valuable reference for monitoring the freshness of goose meat, potentially improving the safety of domestic poultry products.